WHAT WAS THE ASSEMBLY LINE ? - Nye, David E. (Temp - tidsskrift for historie, 2010)
ABSTRACT The Ford assembly line of 1913 was part of a long series of process innovations that began a century before and that have continued since, notably in the lean production system. This paper examines the historical emergence and synthesis of the five essential elements of the classic assembly line – sub-division of work, interchangeability, single-function machines, organization of machines according to the sequence of assembly, and moving work to the worker, typically using gravity slides or moving belts – and further shows that full electrification was an essential precondition for its creation and proper functioning. In contrast, “scientific management” was not important to the creation of the assembly line.